Using the RE-AIM Framework to Evaluate a Physical Activity Intervention in Churches - Melissa Bopp, PhD; Sara Wilcox, PhD; Marilyn Laken, PhD; Steven P. Hooker, PhD; Ruth Saunders, PhD; Deborah Parra-Medina, PhD; Kimberly Butler, BS; Lottie McClorin, MS (Centers for Disease Control and Prevention, 2007)
IntroductionHealth-e-AME was a 3-year intervention designed to promote physical activity at African Methodist Episcopal churches across South Carolina. It is based on a community-participation model designed to disseminate interventions through trained volunteer health directors.MethodsWe used the RE-AIM (Reach, Effectiveness, Adoption, Implementation, and Maintenance) framework to evaluate this intervention through interviews with 50 health directors.ResultsEighty percent of the churches that had a health director trained during the first year of the intervention and 52% of churches that had a health director trained during the second year adopted at least one component of the intervention. Lack of motivation or commitment from the congregation was the most common barrier to adoption. Intervention activities reached middle-aged women mainly. The intervention was moderately well implemented, and adherence to its principles was adequate. Maintenance analyses showed that individual participants in the intervention's physical activity components continued their participation as long as the church offered them, but churches had difficulties continuing to offer physical activity sessions. The effectiveness analysis showed that the intervention produced promising, but not significant, trends in levels of physical activity.ConclusionOur use of the RE-AIM framework to evaluate this intervention serves as a model for a comprehensive evaluation of the health effects of community programs to promote health.